Pendampingan Pembuatan Bahan Ajar Interaktif Berbasis Thunkable sebagai Inovasi Pembelajaran Digital - Melda Agnes Manuhutu; Sherly Gaspersz; Lulu Jola Uktolseja; Wa Ode; Iluminata Iluminata; Antonius Antonius (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2025)
This service activity aims to improve the digital literacy of students and teachers through training in making interactive teaching materials based on the Thunkable application. The activity was carried out in Malibela Complex, Klawalu Village, Sorong City, Southwest Papua Province, with a participatory and hands-on approach. The training was carried out in three stages, namely introduction to the concept of mobile learning and Thunkable application, assistance in the practice of making digital teaching materials, as well as presentation of results and evaluation. The results showed that all participants, both students and teachers, were able to understand and implement the main features of Thunkable, and successfully create prototypes of interactive teaching materials, such as local history applications, junior high school quizzes, and Indonesian teaching materials. In addition to improving technology skills, this activity also encouraged creativity, collaboration and confidence in utilizing digital media for learning. Technical challenges such as limited devices and internet networks were successfully overcome through cooperation between participants. This program proves that no-code-based technology training such as Thunkable can be an effective strategy to encourage digital education transformation, especially in areas with limited access to technology. This program is recommended to be replicated in similar contexts to expand the impact and shape a more adaptive and inclusive learning ecosystem.